Effect of the talc filler on structural, water vapor barrier and mechanical properties of poly(lactic acid) composites - Buzarovska, Aleksandra; Bogoeva-Gaceva, Gordana; Fajgar, Radek (Walter de Gruyter GmbH, 2016)
AbstractPoly(lactic acid) (PLA) based composite films with different content of talc (5–15 wt%) were prepared by the solvent casting method. The effect of talc on morphological, structural, thermal, barrier and mechanical properties of neat PLA was investigated. The PLA/talc composites revealed a polymorphic crystalline structure, as demonstrated by X-ray diffraction (XRD) study and differential scanning calorimetry (DSC) analysis. The PLA/talc composites also exhibited significantly improved barrier properties (up to 55% compared to neat PLA), as shown by water vapor permeability (WVP) tests. The puncture measurements showed improved mechanical properties at lower content of talc (up to 5 wt%), and increased brittleness of the PLA/talc composite films at higher talc concentrations.